Processing technologies of various ethnic fish products consumed in Asian countries: areview - Kapil Deb Nath
Since time immemorial, various communities across different countries have developed their own techniques of preparing traditional fermented ethnic fish products either by drying, smoking, or fermenting them together, or by combining the processes of drying, smoking, and fermentation. Fermentation is a common food preservation technique that improves safety of food, its shelf life, mouth feel, aroma, palatability and nutritional qualities. Fermented foods are thosefoods that are prepared through the regulated escalation of microbes and the enzymatic alteration of dietary components. Fermented fish is produced and consumed throughout the world, and it is an integral feature of many cuisines. It is also an affluent resource of microorganisms as well as a major industry in several countries of the world. These fish items are produced using an environment friendly preservation technology and natural packaging. As a result, food preservation technology becomes low-cost and accessible to the economically weaker section, and it also addresses the issues of food deterioration and food-borne infections. This review primarily aims to underline the process technology of various fermented fish products of some Asian countries and their preparation procedures. In addition, it also highlights the biochemical, microbial, nutritional quality and ethno-medical properties of various fermented fish products